PRELIMINARY RESULTS OF THE ENVIRONMENTAL MAGNETIC STUDIES OF THE SLIGHTLY URBANIZED CITIES. CASE STUDY FROM TRUSKAVETS (UKRAINE) AND MONTPELLIER (FRANCE) - Menshov, O.; Camps, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the present study is the assessment of the general trends for the pollution level of slightly impacted urban environment based on energy-efficient technology. The implementation of this approach is proposed on the examples of Truskavets (Ukraine) and Montpellier (France). The ultimate goal is to produce the preliminary data of the pollution with magnetic measurements. Regarding the anthropogenic pollution of the studied area the slight level of the urbanization must be accepted. The first source of the pollution is the road traffic and the second one is the railway and trams network. Non-urbanized landscape of Truskavets is presented by the forests. The soil types are gleysols. The urbanized soils of Truskavets and Montpellier are the urbozems. The magnetic susceptibility for the non-polluted soil in Truskavets is up to 8-10×10-8 m3/kg, very low values for Ukrainian soils, were registered. At the same time the polluted soils collected from the profiles and under the areal researches near the roadway and railway are characterized by a much higher MS: χ=36-162×10-8 m3/kg. The pollution of the soils were confirmed by the frequency dependence of magnetic susceptibility with the values of χfd= 2-3. The tree leaves from the Montpellier have much higher isothermal remanence along the roadway and tram line comparing with the natural area. The magnetic mineralogical analyses included thermomagnetic studies, hysteresis and remanence acquisition, ARM, and S ratio. The magnetite-like phase as the main magnetic mineral responsible for the magnetic enchantments in polluted soil was identified. At the same time non-polluted soil may contain the small amount of the single-domain (SD) particles and the high coercivity minerals such as haematite and goethite. Our results are valuable for the environmental management companies, centers of environmental monitoring, and geophysical observatories. Low cost, non-destructive and rapid magnetic techniques are promising in monitoring soil and air pollution both in highly anthropogenic impacted areas and at the slightly urbanized sites.